The Effect of High-Intensity Interval Training (HIIT) at Race Pace on Certain Structural and Physiological Abilities and 1500-Meter Running Performance - Murtadha Tahseen Jawad (Sinar Sport Journal, 2025)
The 1500-meter race is considered a middle-distance running event, and this event is characterized by special specifications related to physical fitness elements and physiological indicators to achieve functional adaptation of the organic systems to perform the effort during the race and endure it to achieve the best possible time. This event is characterized by an increase in the effort used (rate of speed) at the beginning of the race and sometimes in the middle of the race, as well as the fast end, which requires the runner to change the specifications of the intensity used. Hence came the importance of research in preparing high-intensity interval training (HIIT) according to the pace of the race in some structural and physiological abilities and the achievement of running the 1500 meters. Hence, The study preparation oriented high-intensity training (HIIT) based on the pace of the race in running the (1500m) and identifying their effecton the study variables. This search is an experimental method on Al-Diwaniyah clubs' players of athletics, specifically middle-distance running for youth, in whose number reached (10) competitors who participated in the sports season (2025). They were randomly assigned to the experimental and control group, with (5) competitors in each group. Study variables did not differ between groups. Those trainings were done in the special preparation phase for both groups for a period of (8) weeks, (3) training units per week. The results after applying high-intensity training (HIIT) according to the pace of the race and the traditional coach training, the researcher concluded that there is an advantage for the experimental group using high-intensity training (HIIT) according to the pace of the race in: Special endurance, maximum oxygen consumption (ml. Per min/kg), lung capacity (L) and achievement of running 1500 meters.